TAX MORALE AS PERCEIVED BY ACCOUNTING PROFESSIONALS - Lopo Martinez, Antonio; Pereira, Ivan Rafael Fassarela (Advances in Scientific and Applied Accounting, 2022)
Objective: This study evaluates firms’ taxpayer morale or the intrinsic motivation to pay taxes and comply with tax rules through the perception of their accounting professionals, specifically whether there is an influence from i) penalties, ii) tax audit probability, iii) rewards, and iv) tax amnesties. The focus on accountants’ perceptions of their clients’ tax morale is more reliable than the taxpayers themselves because they are more likely to report accurate perceptions. Method: Tax morale was measured through a self-applied questionnaire applied between accountants’ professionals that provide their tax services to firms, disclosing their higher or lower accountants’ perception on tax morale of their clients, concerning the four incentives analyzed, captured from 344 Brazilian accountants. Results and Discussion: The research findings indicate that applying punishments and penalties is the most potent instrument for raising tax compliance, along with the perceived likelihood of an audit. In contrast, tax amnesty programs’ successive applications may erode tax morale. Contributions: This research deepens the understanding of what legislators and tax administration can do or not do to encourage more excellent tax morale. Dealing with tax morale is an important issue, as crucial as reforming the entire tax system. Preserving tax morale is relevant to motivate the taxpayer to pay his fair share of taxes, contribute to financing public services, and provide relief to those who may need government assistance.